The impact of distance and the crow hop on medial elbow stress during an interval throwing program. Issue 7 (31st July 2020) - Cross, Austin; Smith, Grace; Gulledge, Caleb; Koolmees, Dylan; Moutzouros, Vasilios; Makhni, Eric; Lizzio, Vincent
Objectives: Rehabilitation programs following ulnar collateral ligament reconstruction include an interval throwing program in order to gradually increase stress and prevent excessive elbow valgus loads. These programs often instruct players to use the crow hop, even at short distances, in order to reduce stress on the reconstructed ligament. The purpose of the study was to evaluate the impact of the crow hop on medial elbow stress at various distances of an interval throwing program. Methods: High school and college-aged baseball players were recruited for this study. Players threw at distances of 30, 45, 60, 90, 120, 150, and 180 feet. At each distance, participants made 3 throws while using a crow hop and 3 throws without using a crow hop with the instruction to throw on an arc. A wearable device recorded elbow torque, arm slot, arm speed, and shoulder rotation. Ball velocity was measured using radar gun. Results: A total of 20 players participated in this study. Overall elbow torque at each distance was 12.9, 20.5, 26.3, 31.9, 34.7, 36.1, and 37.1 Nm, respectively. There was no difference in elbow stress for throws with a crow hop compared to throws without a crow hop at any distance of throwing (p > 0.05). There was no difference in elbow torque for throws at 150 feet compared to 120 feet (p = 0.10) or 150 feet compared to 180 feet (p = 0.83); however, there were significant increases in elbow torque between every other throwing distance (p < 0.05). Conclusions: Medial elbow torque significantly increases at greater throwing distances of a standard interval throwing program, although the effect becomes less pronounced at longer distances as players maximize effort. The crow hop does not affect medial elbow torque at any distance of throwing.